Kontestasi Politik dalam Sastra Hikayat “Tjerita Renggan Sedajoe Anak Radja Kota Aboeng (Orang Ampat Lawang)” - Sastri Sunarti; NFN Atisah; nfn Suryami (Madah: Jurnal Bahasa dan Sastra, 2019)
The political elite contestation since the the past until now is always interesting to be observed, as we can observe in the Palembang’s manuscripts collection entitled “Tjerita Renggan Sedajoe Anak Radja Kota Aboeng (Orang Ampat Lawang)”, then called TRSARKA. This manuscript shows the political elite contestation in the kingdom of Kota Aboeng Negeri Ampat Lawang, South Sumatra. Contestation among the political elite in the manuscript will be analized with the types of leadership and topos (scenes; repetitive story motives) in the traditional literary work. Colleting data uses the literature review that is sourced from the TRSARKA which is one of the Palembang manuscript collections. The manuscipt belongs to the National Library of the Republic of Indonesia under the script code (Br.157.ixc). By using an analytical descriptive approach, the manuscript of TRSARKA is discussed to find the topos. The results of the topos analysis show that the two models of Traditional Malay leaderships that contradict each other in the TRSARKA, namely trustworthy leadership and betrayal leadership. These two leadership models can be interpreted as features of literary work that always describes the character in black and white. Some topos in the TRSARKA manuscript are royal topoi or a fair and prosperous country, the ideal topoi, betrayal to the king topoi, genealogical topoi, and supernatural power topoi.